The Tagamo3 Accent: Linguistic Stylization, Enregisterment, and Social Meaning in Egyptian Digital Discourse - Abdelaziz, Jannah M (AUC Knowledge Fountain, 2026)
This thesis investigates the Tagamo3 Accent (TA), a socially recognizable speech style associated with elite urban Egyptian identity, through a qualitative multimodal discourse analysis of twelve Egyptian TikTok videos, including both naturally occurring lifestyle and influencer content as well as parody and commentary videos that explicitly imitate, discuss, or evaluate the accent. Drawing on theories of enregisterment (Agha, 2003), stylization (Coupland, 2007), and indexicality (Silverstein, 2003; Eckert, 2008), the study examines how TA is linguistically performed, socially recognized, and ideologically circulated within Egyptian digital spaces. The findings suggest that TA does not function as a structurally bounded dialect or geographically fixed accent, but rather as an enregistered speech style composed of recurrent phonetic, prosodic, and bilingual features, including vowel backing and lengthening, hyper-articulated consonants, rising declarative intonation, and patterned Arabic–English code-switching, which acquire social meaning through repetition, parody, and metalinguistic commentary online. The analysis further demonstrates that speakers are labeled as using the “Tagamo3 Accent” regardless of their actual place of residence, indicating that the style operates as a socially indexical category linked to classed and cosmopolitan personae rather than to geographic origin. Within the present dataset, TA is also frequently associated with female-coded influencer discourse and digitally mediated performances of lifestyle and modernity, although this association is not treated as absolute or exclusive. By situating TA within broader discussions of language, identity, and digital mediation, the study contributes to Arabic sociolinguistics and digital sociolinguistic research by examining the emergence and circulation of a hybrid speech style in a contemporary Egyptian context.